Associations of dietary inflammation index and composite dietary antioxidant index with all-cause mortality in COPD patients - Zhao, Sue; Su, Yingjie; Yang, Hongzhong (Frontiers in Nutrition, 2025)
BackgroundFew studies have investigated the effects of both dietary inflammatory index (DII) and composite dietary antioxidant index (CDAI) on mortality in patients with Chronic Obstructive Pulmonary Disease (COPD). Our research aimed to explore the associations between the two indicators with all-cause mortality in COPD patients.MethodsWe conducted a prospective cohort analysis based on data from the six cycles of the National Health and Nutrition Examination Survey (NHANES) dataset from 2007 to 2018. Multivariate Cox proportional hazard models were used to analyze the effects of DII and CDAI on all-cause mortality in COPD. We employed restricted cubic spline (RCS) analysis to examine the dose–response relationship between two indicators and all-cause mortality, used threshold effect analysis to determine the inflection point, and conducted subgroup analysis and interaction tests to verify the stability of the results.ResultsA total of 1,457 COPD patients aged over 40 were enrolled in the study. The median follow-up time was 76.8 months. The multivariate Cox proportional hazards model showed that increased DII was associated with an increase in all-cause mortality (HR (95% CI): 1.11(1.04, 1.18), p = 0.002). In contrast, CDAI was negatively correlated with all-cause mortality (HR (95% CI): 0.95(0.91, 0.99), p = 0.01). The RCS analysis showed a nonlinear correlation between DII or CDAI and all-cause mortality. The maximum pro-inflammatory inflection point of DII was 2.32, while the antioxidant threshold of CDAI is −0.12. Subgroup analyses indicated that the relationship between exposure variables and all-cause mortality was stable in most populations.ConclusionReducing the pro-inflammatory diet or increasing the antioxidant diet can reduce all-cause mortality in COPD patients.